Bacterial spectrum and resistance patterns in corneal infections at a Tertiary Eye Care Center in South China - Wang, Nan; Huang, Qiang; Tan, Yi-Wei; Lin, Li-Ping; Wu, Kai-Li (International journal of ophthalmology, 2016)
AIM： To investigate the spectrum and antibiotic susceptibility of bacteria isolated from patients with suspected corneal infections in Zhongshan Ophthalmic Center in South China over the past four years retrospectively. METHODS： Totally 1943 corneal scrapes from patients with corneal infections from 2010 to 2013 were cultured and processed using standard microbiological procedures to identify bacterial isolates. Simultaneously, the bacterial isolates were tested for antibiotic susceptibility to 8 antibiotics （ceftazidime, cefuroxim, cefazolin, levofloxacin, ofloxacin, neomycin, tobramycin, chloramphenicol） using the Kirby-Bauer disc diffusion technique. RESULTS： Of the total 1943 scrapes, 397 （20.43%） were culture-positive, of which 294 （74.06%） were gram- positive （GP） and 103 （25.94%） were gram-negative （GN） bacteria. Of the GP organisms, the most prevalent genera were Staphylococcus spp. （56.17%, n=223）, Kocuria spp. （5.29%, n=21） and Micrococcus spp. （1.26%, n=5）. On the other hand, the most prevalent genera were Pseudomonas spp. （12.85%, n=51）, Burkholderia spp. （2.02%, n=8） and Acinetobacter spp. （1.51%, n =6） for the GN organisms. Among five antibiotics that have eye drop products, the resistant to neomycin of GP （7.82%, 95% Ch 4.72%-10.92%） and GN isolates （9.71%, 95% Ch 4.01%-15.41% ） was lowest, while the resistant to chloramphenicol was highest （GP： 34.35%, 95% Ch 28.92%-39.78%; GN： 60.19%, 95% Ch 50.74%-69.64%）. CONCLUSION： Staphylococcus spp. was the most common bacterial pathogens isolated from patients with corneal infections in this setting. High percentages of GP and GN bacteria were mostly susceptible to neomycin and highly resistant to chloramphenicol.